Epidémiologie des Malformations Congénitales Visibles à la Naissance à Yaoundé - Kamla, Joël Igor; Kamgaing, Nelly; Nguifo Fongang, EJ; Fondop, Joseph; Billong, Serge; Djientcheu, Vincent (HEALTH SCIENCES AND DISEASE, 2017)
ABSTRACT Introduction. Congenital malformations are one of the main causes of neonatal morbidity and mortality. Epidemiological data on this topic are largely unknown in the Cameroon population. This prospective multicentre study aimed at bringing more data on the qualitative and quantitative aspects of congenital malformations in Yaoundé. Methods. This was a cross sectional descriptive prospective study. We studied all newborns presenting one or more malformations detectable at birth in 10 selected and representative maternities for one year. Data of interest were type of malformation, newborn anthropometric parameters, sociodemographic records of parents, obstetrical data, past medical history of the mother, history of previous malformations, abortion or still birth, irradiation, fetal toxic drugs including folic acid around the conception. Results. The prevalence was 9 per 1000 births. The most common types of malformations were (per 1.000 births) polydactyly 2.1; clubfeet 1.1, Neural tube defects 1.4; Hydrocephalus 1.1; oro-facial clefts 0.9; and abdominal parietal defects 0.7. The pair myelomeningocele and hydrocephalus was common polymalformation. The sex ratio was 1.1. Mothers of malformed babies were mostly found in the age group 26 to 35 years (49.6%), single, housewives with a secondary education level. Suspected risk factors were maternal fever during the first trimester (31.4 %), past history of spontaneous abortions (23.4 %), primiparous mothers (36.6 %), and absence folic acid supplementation in periconceptional period (100 %). Conclusion. Congenital malformations are relatively frequent in Yaoundé. There is no national prevention strategy. RÉSUMÉ Introduction. Les malformations congénitales représentent l’une des principales causes de morbidité et de mortalité néonatale. Les données épidémiologiques sur ce sujet sont rares au Cameroun et non représentatives de la population d’où cette étude prospective visant à contribuer à l’analyse des aspects qualitatifs et quantitatifs de ces malformations à Yaoundé. Méthodologie. Nous avons recensé pendant un an tous nouveau-nés présentant une ou plusieurs malformations décelables à la naissance dans 10 maternités sélectionnées et représentatives. Résultats. La prévalence était de 9 cas pour 1000 naissances. Les types de malformations les plus fréquentes étaient (pour 1000 naissances) la polydactylie (2,1) ; les pieds bots (1,1), les anomalies de fermeture du tube neural (1,4) ; l’hydrocéphalie (1,1) ; les fentes orofaciales (0,9) ; et le défect pariétal abdominal (0,7). L’association myéloméningocèle et hydrocéphalie était la polymalformation la plus fréquente. Le sexe ratio était de 1,1. Les nouveau-nés malformés étaient issus pour la plupart des mères âgées entre 26 et 35 ans (49,5 %), célibataires (61,7 %), ménagères (28,7 %), avec un niveau d’étude secondaire (56,4 %). Les facteurs de risques suspectés sont la fièvre maternelle au premier trimestre (31,4 %), les antécédents d’avortement spontané (23,4 %), la primiparité (36,6 %) et l’absence de supplémentation périconceptionnelle en acide folique (100 %). Conclusion. Les malformations congénitales sont des pathologies fréquentes à Yaoundé. Il n’existe pas de stratégie nationale de prévention.